Low Pressure Low Frequency Jet Ventilation: Techniques, Safety and Complications...American Broncho-Esophagological Association during the Combined Otolaryngology Spring Meeting (COSM) on May 1st 2019, Austin, TX. - Myint, Calvin W.; Teng, Stephanie E.; Butler, Jennifer J.; Griffeth, Jacline V.; Fritz, Mark A.; Meiler, Steffen E.; Postma, Gregory N. (Annals of Otology, Rhinology & Laryngology, 2022)
Objective: Manual jet ventilation is a specialized oxygenation and ventilation technique that is not available in all facilities due to lack of technical familiarity and fear of complications. The objective is to review our center's 15 year experience with low pressure low frequency jet ventilation (LPLFJV). Methods: Retrospective review of procedures utilizing LPLFJV from 2005 to 2019 were performed collecting patient demographic, surgery type and complications. Fisher exact test, Chi square, and t -test were used to determine statistical significance. Results: Four hundred fifty-seven patients underwent a total of 891 microlaryngeal surgeries—279 cases for voice disorders, 179 for lesions, and 433 for airway stenosis. The peak jet pressure for all cases did not exceed 20 psi and average peak pressure for the last 100 procedures in this case series was 14.9 ± 4.6 psi. The average lowest oxygen saturation for all cases was 95% ± 0.6%. Brief intubation was required in 154 cases (17%). Surgical duration was significantly longer for cases requiring intubation P <.001. The need for intubation was not associated with smoking or cardiopulmonary disease, but was strongly associated with body mass index (BMI). Intubation rates were 7% for normal weight (BMI < 25, N = 216), 13% for overweight (BMI 25-30, N = 282), 24% for obese (BMI 30-40, N = 342), and 37% for morbidly obese (BMI > 40, N = 52) patients. Three patients developed respiratory distress in the recovery unit and 2 patients required intubation. Conclusion: LPLFJV assisted by intermittent endotracheal intubation is an exceedingly safe and effective intraoperative oxygenation and ventilationmodality for a broad variety of laryngeal procedure.